Urban heat: an increasing threat to global health. (25th October 2021) - Tong, Shilu; Prior, Jason; McGregor, Glenn; Shi, Xiaoming; Kinney, Patrick
Abstract : Shilu Tong and colleagues describe the health consequences of extreme urban heat and the priorities for action and research to mitigate the harms